Strategies to improve customer satisfaction with Industrialised Building System (IBS) houses and IBS adoption using Quality Function Deployment (QFD) application : a Malaysia based study / Nuzul Azam Haron - Nuzul Azam, Haron (2012)
The Malaysian government has brought the Industrialised Building System (IBS) to the attention of all professionals in this industry. Due to certain barriers, the actual projection of the IBS adoption could not be achieved. One of the factors identified is the lack of customer satisfaction with IBS houses. This research aims to determine the factors pertaining to customer satisfaction of IBS houses, the strategies to improve customer satisfaction, to determine IBS adoption factors and the strategies to improve IBS adoption in the Malaysian construction industry. This research methodology uses a mixed method approach. The research process was conducted in four (4) phases. Relevant respondents were divided into two groups, namely, the IBS house occupiers and the construction industry stakeholders. The quantitative study is based on a self-administered questionnaire survey. Purposive sampling was carried out to determine the sample from three types of IBS houses. Data were obtained from 391 IBS house occupiers to determine customer satisfaction in the first part of the first phase. In addition, data from 105 valid respondents of construction stakeholders were obtained to determine IBS adoption factors in the second part of the first phase. Then, the researcher continued the study using a structured focus group discussion, qualitatively, in the second and third phase. Respondents who are IBS house occupiers, construction stakeholders and academicians took part in the discussion. The QFD matrixes were developed from the Quality matrix and Function matrix, which led to the compilation of the QF matrix. The researcher also developed a list of strategies on how to improve customer satisfaction on IBS house development and strategies on how to improve the IBS adoption in the Malaysian construction industry. The researcher used descriptive and gap analysis for the quantitative study. A statistical analysis was conducted to confirm the reliability of the instruments used. The qualitative study of the structured focus group discussion is continued further by using QFD application. Lastly, the researcher applied semi structured interviews to achieve its validity in phase four (4). Respondents for the validation process consisted of ten (10) experts – academicians, and construction stakeholders. The study discovered nine (9) customer satisfaction factors related to IBS house construction. The nine (9) factors were identified as critical factors in IBS adoption. Five (5) strategies were identified from the QFD application on how to improve customer satisfaction in IBS house construction and five (5) strategies were identified from the QFD application on how to improve IBS adoption. Several major recommendations to improve customer satisfaction and to enhance IBS adoption were made. This research will contribute to four (4) kinds of new knowledge. First, it will provide strategies to address the issue concerning the lack of customer satisfaction in IBS housing projects. Second, it will provide strategies to improve and enhance IBS adoption. Third, it highlights the major roles of related organizations to enhance the IBS adoption industry. Finally, yet importantly, it provides new knowledge and a new dimension to QFD application in the IBS planning and management system.